2017
DOI: 10.1016/j.soilbio.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Linking microbial community composition to C loss rates during wood decomposition

Abstract: Although decaying wood plays an important role in global carbon (C) cycling, how changes in microbial community are related to wood C quality and then affect wood organic C loss during wood decomposition remains unclear. In this study, a chronosequence method was used to examine the relationships between wood C loss rates and microbial community compositions during Chinese fir (Cunninghamia lanceolata) stump decomposition. Our results showed that microbial community shifted from fungi-dominated at early stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…and Betula sp., where they make up, respectively, 12%, 20% and 32% of all sequences. As bacteria seem to benefit from high wood moisture (Hu et al, 2017), it can be anticipated that they will make a contribution to decomposition under the conditions of this experiment.…”
Section: Microbial Distribution Related To Sapwood and Heartwoodmentioning
confidence: 99%
“…and Betula sp., where they make up, respectively, 12%, 20% and 32% of all sequences. As bacteria seem to benefit from high wood moisture (Hu et al, 2017), it can be anticipated that they will make a contribution to decomposition under the conditions of this experiment.…”
Section: Microbial Distribution Related To Sapwood and Heartwoodmentioning
confidence: 99%
“…Wood traits involved in C quality and nutrient availability strongly influence microbial community on decomposition processes (Manning, Rosemond, Gulis, Benstead, & Kominoski, 2018;van der Wal et al, 2007). These traits also influence how microbial community composition might respond to changes in the environment (e.g., warming and drought; Lavorel & Garnier, 2002;Matulich & Martiny, 2015), whereas microbial taxa determine microbial decay capacity and decomposition rates (Hu et al, 2017). Therefore, wood traits may play a dominant role in determining the microbial taxa for wood decomposition across global climate gradients.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The elemental analysis suggested that long-term mowing practice had major impacts on the elemental composition of SOM. The lower H / C ratio indicated more aromatic compounds or higher aromaticity and saturability, and the higher O / C ratio indicated more carboxyl groups, phenol or carbohydrates with oxygen (Ma et al, 2001;Steelink, 1985;Kim et al, 1991). 13 C NMR apparently differentiated the lignin C (including alkyl, N-alkyl and aryl C) and carbohydrate C (including O-alkyl, di-Oalkyl, carbonyl and carboxyl C) (Hu et al, 2017).…”
Section: Stability Of Som Impacted By Different Mowing Treatmentsmentioning
confidence: 99%